Regional variation in δ13C of coral reef macroalgae. (4th May 2020) - Lovelock, Catherine E.; Reef, Ruth; Raven, John A.; Pandolfi, John M.
Abstract: Macroalgae are important components on coral reefs that underpin food webs but are also indicators of declines in coral reef condition. The sensitivity of macroalgal communities to environmental factors, including climate and pollutants from the land, is important for the future state of coral reefs. We assessed regional variation in the photosynthetic physiology of macroalgae on the Great Barrier Reef and Moreton Bay, Queensland, Australia, using δ 13 C, tissue chemistry, and metabolic indicators over broad environmental gradients from six sites spanning 13° of latitude and varying distance from shore. Our data set included 568 samples from 54 genera and 19 macroalgal orders. The δ 13 C of tissues had a strong taxonomic basis (explaining 66% of the variation in δ 13 C), varying significantly among algal orders. Particularly low values of δ 13 C, indicating direct use of CO2(aq) in photosynthesis, were mainly associated with lineages within the Rhodophyta. We observed declines in δ 13 C with increasing depth (inshore only) and latitude, from offshore to inshore sites and with increasing tissue N and N : P ratio. Variation in δ 13 C of tissues among macroalgal lineages suggests evolution of a range of CO2 acquisition pathways. Patterns in δ 13 C availability are most consistent with higher availability of CO2(aq) in cooler water and inshore sites. δ 13 C in macroalgae could provide an important tool for monitoring changes in CO2(aq) with increasing atmospheric CO2, with changes in ocean circulation and with changes to runoff from the land to the coastal oceans.